Acid-alternating-base (AAB) technology for blockage removal and enhanced oil recovery in sandstone reservoirs. (1st March 2018) - Zhu, Daoyi; Hou, Jirui; Wang, Jianfei; Wu, Xuan; Wang, Peng; Bai, Baojun
Abstract: An acid-alternating-base (AAB) system was evaluated based on ability to generate CO2 in a reservoir for blockage removal and oil recovery improvement. CO2 generation processes were measured in both the containers and the porous media for comparison. Optimal CO2 production and generating efficiency were obtained by adjusting the acid molar concentration ratio and system mass concentration. The AAB system had a good displacement efficiency in both homogeneous and heterogeneous porous media. Enhanced oil recovery (EOR) mechanisms of the acid-alternating-base (AAB) technology were then investigated. The basic solution of the AAB system can lower interfacial tension (IFT) between crude oil and displacing fluid; the CO2 generated in formation can swell oil and reduce oil viscosity; the heat released by the acid-base reaction can dissolve organics and increase oil recovery, and the pressure fluctuation caused by CO2 generation process and inorganic dissolution can also contribute to the improvement of oil recovery. This technology has been successfully applied in the offshore Bohai Bay Field approximately 200 km east of Beijing.